John Calvin : Student of the Church Fathers, Vol. 2 - S. Lane, Anthony N. (Late Antiquity and Medieval Studies E-Books Online, Collection 2026, 2026)
This volume continues the approach of the original John Calvin: Student of the Church Fathers. It begins with eighteen methodological theses on how to study Calvin's use of the patristic and medieval tradition. There are comprehensive studies of his use of Tertullian, Ambrose, Augustine, Cyril of Alexandria, and Peter Lombard. Each of these is followed by tables with details of Calvin's citations and their sources. Finally, there are comprehensive annotated bibliographies of the secondary literature on the topic published from 1800 to 1999 and from 2000 to 2024.